Business Design and Feasibility of Humblezing Store Branch Establishment in South Jakarta - Alya Raisa Khanza; Endang Chumaidiyah; Maria Dellarosawati (Al Tijarah, 2021)
Feasibility analysis is done to determine a business design is feasible to run. The purpose of this research is to find out if Humblezing established an offline store branch in South Jakarta is feasible or not to run. Humblezing is a clothing line business that sells clothing products such as outerwear, shirts, jackets, pants, and bag with the concept of modern adventurwear. Humblezing sells online and offline with the first store in Bandung. The feasibility measurement pay attention to market aspects, technical aspects and financial aspects which will be projected for 5 years. The tools that used in this research are Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PBP), Sensitivity Analysis and Risk Analysis. Based on the results of the feasibility analysis, show that the NPV value is IDR 185,343,832, IRR 38%, PBP for 3.81 years with a MARR value is 11,25%. Sensitivity measurements on the increase in product costs sensitive at 9.31%, increase in labor costs at 14.07%, decrease in selling prices at 3.19% and decrease in market demand at 2.33%. Furthermore, the estimated accumulated risk of establishing a Humblezing offline store branch includes market risk, operational risk and financial risk is 5.50%.